ИССЛЕДОВАНИЕ ПРОЧНОСТИ И ЖЕСТКОСТИ ПЛАСТИНЫ, ПОДКРЕПЛЕННОЙ РЕБРАМИ НА ОДНОЙ ПЛОСКОСТИ. Issledovanie pročnosti i žestkosti plastiny, podkreplennoj rebrami na odnoj ploskosti - Molnár, Sándor (Periodica Polytechnica Mechanical Engineering, 1985)
Stress analysis of the plates stiffed Ьу ribs оп one side was carried оut with the variation methods of Lagrange and Reissner. It was worked оut а computational program for solution equation of equilibrium and joining conditional system determined Ьу Lagrange’s method considering the different boundary conditions. Numerical results have solution, then former ones.